Sound localization with head movement: implications for 3-d audio displays - McAnally, Ken I.; Martin, Russell L. (Frontiers in Neuroscience, 2014)
Previous studies have shown that the accuracy of sound localization is improved if listeners are allowed to move their heads during signal presentation. This study describes the function relating localization accuracy to the extent of head movement in azimuth. Sounds that are difficult to localize were presented in the free field from sources at a wide range of azimuths and elevations. Sounds remained active until the participants’ heads had rotated through windows ranging in width of 2°, 4°, 8°, 16°, 32°, or 64° of azimuth. Error in determining sound-source elevation and the rate of front/back confusion were found to decrease with increases in azimuth window width. Error in determining sound-source lateral angle was not found to vary with azimuth window width. Implications for 3-d audio displays: The utility of a 3-d audio display for imparting spatial information is likely to be improved if operators are able to move their heads during signal presentation. Head movement may compensate in part for a paucity of spectral cues to sound-source location resulting from limitations in either the audio signals presented or the directional filters (i.e., head-related transfer functions) used to generate a display. However, head movements of a moderate size (i.e., through around 32° of azimuth) may be required to ensure that spatial information is conveyed with high accuracy.